Meningkatkan Kreativitas Dan Keterampilan Sosial Anak Berkebutuhan Khusus Perspektif Teori Neurosains Menurut Santiago Ramon Y Cajal - Umu Lailatussyarifah; Muhammad Zainudin; Alisa Kurniawati; Muhammad in’am Akmalilahya; Rahayu Sulistyawati; Tiara Safna Annida (Jurnal Ilmu Pendidikan, 2025)
This journal examines the enhancement of creativity and social skills among children with special needs at SLB Marsudi Putra 1 Bantul through the lens of Santiago Ramón y Cajal's neuroscience theory. The study employs a qualitative case study approach, utilizing observation, interviews, and documentation to analyze the implementation of neuroplasticity in activities such as art, culinary arts, sewing, batik-making, and drumband. The research aims to identify neuroscience strategies for boosting creativity via new neural pathway formation and social skills through repeated interactions, while uncovering challenges like the need for repetitive learning among children with hearing impairments, intellectual disabilities, and autism. Findings indicate that individualized and routine approaches effectively strengthen brain synapses, aligning with the principle "neurons that fire together, wire together." Field methods involved data triangulation from teachers and observations of 60 elementary-to-high school students, focusing on weekly skills training. Key findings include creativity gains through multisensory arts and social skills improvements via cooperative learning, despite obstacles like IQ variations and low concentration. Cajal's neuroscience approach proves optimal at SLB Marsudi Putra 1 Bantul for maximizing special needs children's potential, with recommendations for in-depth talent assessments and parent-teacher collaboration.